Social Equity Considerations in Programming for Climate Resilience - Soriaga, Rowena; Cabriole, Marie Aislinn; Hellin, Jon; Gonsalves, Julian (CGIAR System Organization, 2024)
Fairness and justice are fundamental principles of social equity, a core theme of the CGIAR research initiative on Building Systemic Climate Resilience against Climate Variability and Extremes (ClimBeR). This policy brief leverages the research process to develop a sourcebook focused on social equity, inclusiveness, gender, and other foundational aspects of ClimBeR. Over 50 online publications, primarily from 2021 to 2023, were reviewed and categorized according to the CGIAR ClimBeR framework on Social Equity in Climate-Resilient Agriculture.